2007
DOI: 10.1523/jneurosci.3801-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Slow Conformational Changes of the Voltage Sensor during the Mode Shift in Hyperpolarization-Activated Cyclic-Nucleotide-Gated Channels

Abstract: Hyperpolarization-activated cyclic-nucleotide-gated (HCN) channels are activated by hyperpolarizations that cause inward movements of the positive charges in the fourth transmembrane domain (S4), which triggers channel opening. If HCN channels are held open for prolonged times (Ͼ50 ms), HCN channels undergo a mode shift, which in sea urchin (spHCN) channels induces a Ͼ50 mV shift in the midpoint of activation. The mechanism underlying the mode shift is unknown. The mode shift could be attributable to conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 39 publications
8
75
2
Order By: Relevance
“…The shift of the Q-V curve was found to correlate with the development of slow inactivation of the sodium conductance. Although the same type of shift was later found in L-type Ca channels (10), the Shaker K channel (8), the HERG K channel (11), the bacterial Na channel (NaChBac) (12), and channels in the hyperpolarization-activated cyclic nucleotide-gated (HCN) family (13)(14)(15), it could not, in every case, be associated with entry into the slow-inactivated state of the channel. For example, the inactivation-deficient mutant S631A of HERG showed the same Q-V shift as the wild type (11).…”
mentioning
confidence: 76%
“…The shift of the Q-V curve was found to correlate with the development of slow inactivation of the sodium conductance. Although the same type of shift was later found in L-type Ca channels (10), the Shaker K channel (8), the HERG K channel (11), the bacterial Na channel (NaChBac) (12), and channels in the hyperpolarization-activated cyclic nucleotide-gated (HCN) family (13)(14)(15), it could not, in every case, be associated with entry into the slow-inactivated state of the channel. For example, the inactivation-deficient mutant S631A of HERG showed the same Q-V shift as the wild type (11).…”
mentioning
confidence: 76%
“…Recently, it was shown that the voltage-dependent activation of the HCN channel cloned from sea urchin sperm (spHCN) can shift between two modes depending on the previous activity (53,133,246). In mode I, gating charge movement and channel opening occur at very negative potentials, while in mode II, both processes are shifted to Ͼ50 mV more positive potentials (133).…”
Section: A Transmembrane Segments and Voltage Sensormentioning
confidence: 99%
“…As an alternative technique to study I Ks voltage sensing, we chose to pursue a fluorescence assay, voltage clamp fluorometry (17), which tracks changes in emission from a fluorophore attached to the extracellular end of the voltage-sensing fourth transmembrane segment of KCNQ1 (S4) as its environment changes during voltage sensing. This method has been used previously to assay voltage sensor movements in other members of the superfamily of voltage-gated cation channels (17)(18)(19).…”
Section: Embers Of the Superfamily Of Voltage-gated Cation Channelsmentioning
confidence: 99%